Daya saing dan keberlanjutan destinasi wisata desa kabupaten Kutai Kartanegara - Rian Hilmawan; Yesi Aprianti; Muliati; Andriawan Kustiawan (Journal of Tourism and Economic, 2023)
This research aims to descriptively identify the competitiveness of tourist destinations in Kutai Kartanegara, East Kalimantan Province, according to the perspective of stakeholders, namely the local government and owners of tourist destination. It then classifies the strengths, weaknesses, opportunities and threats under SWOT Analysis framework. This study also explains the sustainability of tourist destinations measured from economic, socio-cultural and environmental componentsUsing qualitative descriptive technique, our data. were taken from secondary and primary sources, namely from the Tourism Office of Kutai Kartanegara, Indonesian. and through sample field visits by interviewing informants from Benua Elai (Belai) Tourism Village (Desa Wisata Benua Elai) in Sub-District of Loa Janan. The research results show that the competitiveness of tourist destinations in Kutai Kartanegara has comparative and competitive advantages. Comparatively, natural tourism has 74 destinations, followed by cultural tourism with 157 destinations. There are also 21 artificial tourist destinations. In terms of competitive advantage, institutional support from the district government in supporting the development of community-managed tourist destinations through Kelompok Sadar Wisata (Pokdarwis) has been carried out. From the aspect of sustainability, tourist destinations such as Desa Belai have the potential to improve well-being of surrounding communities, though the position of tourist destinations has been threatened by large-scale mining activities. These coal mining explorations may harm sustainability of village tourism and its prospect to be leading growth sector.